“Gleaning a lot from the history and physical exam,” and “reasonably confident without imaging”: a qualitative study of primary care clinicians' management of patients with low back pain - Lynn Haslam-Larmer; Kathleen E. Norman; Andrea M. Patey; Isabella M. Thomas; Michael E. Green; Jeremy M. Grimshaw; Jill A. Hayden; Jan Hartvigsen; Noah M. Ivers; Hazel Jenkins; Simon D. French (BMC Primary Care)
Abstract Background Routine seeking of imaging for patients with low back pain is not concordant with the evidence-based recommendation that imaging is rarely of diagnostic value. Inappropriate imaging is a waste of resources and can lead to undesirable downstream effects for individuals and health systems. To develop effective strategies to reduce unwarranted referrals for imaging in primary care, we must understand the drivers for, and barriers to, guideline-adherent practice. We explored clinicians’ views to identify the dominant influences on clinicians as they choose to pursue, or avoid, imaging for their patients with low back pain. Methods We interviewed a purposeful sample of 47 primary care clinicians (14 physiotherapists, 18 chiropractors, 15 physicians) throughout Ontario, Canada, with a guide based on the Theoretical Domains Framework (TDF). We investigated clinicians’ views about their use of imaging in the management of low back pain. Interviews were recorded and transcribed verbatim. We analysed transcripts, then identified themes within TDF domains. Results Most clinicians reported that, for most clinical encounters, they adhered to guideline recommendations about imaging. Many clinicians across disciplines expressed the following themes: (1) imaging may result in an incidental finding or otherwise cause harm to patients, and drive up health system costs (TDF domain Beliefs about consequences); (2) clinicians were confident in their abilities to diagnose, to explain to patients the rationale for not recommending imaging, and to respond to their needs (domains Beliefs about capabilities; Skills). Many clinicians identified that patients occasionally want the validation that imaging provides (domain Social influences). Some clinicians described the value of imaging to corroborate a diagnosis (domain Beliefs about consequences). Conclusions This study is the first to examine influences on imaging behaviours of a large interprofessional sample of primary care clinicians in Canada. Even among knowledgeable, skilled, confident clinicians who reported mostly adhering to guideline recommendations, there are potential influences on deviating from guideline-adherent care.